2011
DOI: 10.4061/2011/642460
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Supports for the Immobilization of β-Glucosidase

Abstract: A set of supports were screened for the immobilization of a partially purified extract of β-glucosidase from Aspergillus sp. These supports, namely, Eupergit, Amberlite, alginate, gelatin, polyvinyl alcohol- (PVA-) based matrices (Lentikats), and sol-gel, have proved effective for the implementation of some other enzyme-based processes. The initial criterion for selection of promising supports prior to further characterization relied on the retention of the catalytic activity following immobilization. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 44 publications
5
22
0
Order By: Relevance
“…The optimal pH for both immobilized and free forms of the enzyme was 4.0 (data not shown). Roughly similar patterns, where optimum pH is not changed with immobilization, were reported previously (D'Souza and Kubal, 2002;Tu et al, 2006;Figueira et al, 2011). AbdElGhaffar and Hashem, (2010) found that the maximum activity was at pH 7.0 for free cellulase and cellulase immobilized on chitosan-L-glutamic acid-GDA (1%), pH 8.0 for cellulase immobilized on chitosan-4-aminobutyric acid-GDA (1%).…”
Section: Ph Profilesupporting
confidence: 84%
See 3 more Smart Citations
“…The optimal pH for both immobilized and free forms of the enzyme was 4.0 (data not shown). Roughly similar patterns, where optimum pH is not changed with immobilization, were reported previously (D'Souza and Kubal, 2002;Tu et al, 2006;Figueira et al, 2011). AbdElGhaffar and Hashem, (2010) found that the maximum activity was at pH 7.0 for free cellulase and cellulase immobilized on chitosan-L-glutamic acid-GDA (1%), pH 8.0 for cellulase immobilized on chitosan-4-aminobutyric acid-GDA (1%).…”
Section: Ph Profilesupporting
confidence: 84%
“…Calsavara et al (2001) reported that t ½ of free and immobilized cellobiase at 65 ºC were 2.1 and 21.3 h, respectively. This is probably due to the formation of multiple covalent bonds between β-glucosidase and the support that reduce conformational flexibility and thermal vibration, thus preventing the immobilized protein from unfolding and denaturing (Mateo et al, 2000;Wang et al, 2009;Figueira et al, 2011). The deactivation rate constant at 65 ºC for the immobilized β-glucosidase is 9.5x10 -3 / min, which is lower than that of the free form (12.53x10 -3 / min).…”
Section: Thermal Stabilitymentioning
confidence: 97%
See 2 more Smart Citations
“…A similar improvement of the stability of bgl has been reported previously, where different materials were used for the covalent immobilization of the enzyme (Ahmed et al, 2013). The observed improvement in the thermal stability of immobilized bgl comparing to the free enzyme may result from the combined action of a reduced molecular mobility and an improved conformational stabilization of the enzyme induced by the covalent bonding of bgl to the nanomaterials (Figueira et al, 2011;Patila et al, 2016a). It is interesting to note that bgl/GO-OA-γFe exhibits significant higher halflife constant than bgl/GO-γFe.…”
Section: Thermal Stability Of Bglsupporting
confidence: 54%